Penentuan Niat Mahasiswa IAIN Shaikh Abdurrahman Siddik Bangka Belitung dalam Berwirausaha - Wulpiah Wulpiah; Kiki Listari (Universitas Islam Raden Rahmat, 2025)
This empirical study aims to determine the factors that influence the intention of IAIN Syaikh Abdurrahman Siddik students to become entrepreneurs. Discussing in an implemented manner whether environmental factors (access to capital, access to information and access to social networks) influence the intention of IAIN students to become entrepreneurs? Do skill factors (communication skills, ability to develop business strategies and ability to operate IT devices) influence the intention of IAIN students to become entrepreneurs? Do orientation factors (entrepreneurial knowledge, entrepreneurial desire) influence the intention of IAIN students to become entrepreneurs? Do obstacles (financial risk, lack of expertise, social risk, and lack of commitment) influence the intention of IAIN students to become entrepreneurs? This study is a quantitative study with descriptive analysis techniques, and inferential analysis, using Multiple Linear Regression, and the assistance of SPSS 23.0 software. The population of this study were IAIN Bangka Belitung students. Respondents in this study were selected using purposive sampling techniques. The population of the study was 500 students from three faculties, so that a sample of 125 students was obtained. Based on the research results, it can be concluded that environmental factors, skills, orientation, and obstacles have a positive influence on entrepreneurial intentions.